Peningkatan Speaking Melalui Metode Debat - Khudriyah Khudriyah; Nur Munir; Mujahidin Mujahidin (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
English, especially speaking, is very important for students to master it, especially in this digital era, alot of information is conveyed using English orally. This assistance aimed to overcome the very low speaking ability of BEM STIT al Urwatul Wutsqo members. One of them is the debate method. This mentoring was attended by 20 students. The research results shows that the debate method works very effectively and has a positive impact, where speaking skills increase significantly, as evidenced by the results of the pretest and posttest with paired sample test with the results t count > t table (- 8, 929 > 2, 172913), and 0.000 < 0.05, then this assistance is declared successful.